Examination of the prevalence of Escherichia coli containing the CTX-M-1 gene in urinary tract infection samples collected from Zanjan hospitals, Iran. Issue 2 (2021) - Nori, Khatereh; Dabir, Sasan; Mohammadi, Jamal; Alizadeh, Ali; karimi, Fatemeh; Mahmoudi, Sara; Pournajafi, Amir
No abstract available